Controlling spin polarized band-structure by variation of vacancy intensity in nanostructures. (3rd February 2015) - Kamali, S; Kilmametov, A; Ghafari, M; Itou, M; Hahn, H; Sakurai, Y
Abstract: In this study, the magnetic properties of FeAl alloys with different grain sizes produced by high-pressure torsion were probed by means of magnetic Compton scattering. The measurements were performed at 300 and 10 K. Magnetic Compton profiles of nanocrystalline (35 nm) and ultrafine-grained (160 nm) FeAl alloys were analyzed in terms of the integral area, the width, and the distinctive dip intensity at low momenta. The changes in total magnetic moment and the strength of spin-polarization of itinerant electrons are assumed to be caused by vacancies induced during the preparation of the samples. Despite local disordering due to interfacial regions and deviations in perfect stoichiometry for B2 structure, the effect of vacancies is considered as the major magnetic state contributor.